Chronic Vitamin E Deficiency in Rural Bangladeshi Women. (7th June 2021) - Gurung, Sabi; Schulze, Kerry Jean; Shamim, Abu Ahmed; Shaikh, Saijuddin; Ali, Hasmot; Wu, Lee S-F; Udomkesmalee, Emorn; Eggersdorfer, Manfred; Kraemer, Klaus; Labrique, Alain; Jr., Keith West; Christian, Parul
Abstract: Objectives: Vitamin E deficiency (VED) appears to be common in rural areas of South Asia, with prevalence of ≥ 50% reported among women of reproductive age. Long term deficiency may impart neurological damage, but little information exists about persistence of VED. We provide initial estimates of chronic VED (CVED) in women of reproductive age living in Gaibandha District, a typical rural setting in NW Bangladesh. Methods: We assessed α-tocopherol concentrations by HPLC in early pregnancy and 3-month postpartum (PP) plasma samples of women participating in biochemical sub-studies of JiVitA-1 (n = 2, 319), a cluster-randomized, placebo-controlled, weekly vitamin A or β-carotene supplementation trial from 2001–7, and JiVitA-3 (N = 2, 073), a cluster-randomized, daily multiple micronutrient (MMS) versus iron-folic acid (IFA) supplementation trial from 2008–12. VED was conventionally defined by an α-tocopherol concentration < 12 μmol/L and CVED as α-tocopherol < 12 μmol/L at both early pregnancy and postpartum assessments, an interval spanning a median (IQR) of 9.4 (2.8) months. Results: Across both trials combined (N = 4, 392), the mean ± SD plasma α-tocopherol concentration and prevalence of VED in early pregnancy and at 3 months post-partum was 11.28 ± 4.07 and 10.86 ± 4.41 μmol/L, and 53.5% and 42.2%, respectively. In JiVitA-3, the post-partum prevalence of VED among women not previously receiving MMS (containing 15 mg of vitamin E as all- rac -α-tocopheryl acetate) was 57.5% (vs 42.5% among MMS recipients, p < 0.001). The prevalence of CVED among women in both trials combined was 32.0% (34.45% in JiVitA-1 and 26.65% in JiVitA-3, IFA group only). Across a maternal age range of 11–43 [median: 20 (IQR: 8) years, risk of CVED decreased comparably per year of age in the JiVitA-1 [OR = 0.94 (95% CI: 0.93–0.95)] and JiVitA-3 [OR = 0.93 (95% CI:0.92–0.95)] trials. Conclusions: In rural NW Bangladesh, where over half of women enter pregnancy vitamin E-deficient, about one-third are also deficient postpartum, ∼10 months later, providing a provisional estimate of chronic maternal vitamin E deficiency in a South Asian setting. Funding Sources: Bill & Melinda Gates Foundation (Grant GH614, OPP1141435) and US Agency for International Development (AID (HRN-A-00–97-00015–00).